Dataset: Small area estimates of BMI distribution by age, sex and lower tier local authority (England) - Amies-Cull, B; Wolstenholme, J; Cobiac, L; Scarborough, P (University of Oxford, 2022)
Published final results from the paper "Estimating BMI distributions by age and sex for local authorities in England: a small area estimation study". This paper used a small area estimation method to estimate the distribution of BMI for local areas in England, by age and sex.